STUDIES ON INDIAN TANYMECINA (TANYMECINI, BRACHYDERINAE, CURCULIONIDAE, COLEOPTERA) I. GENUS TANYMECUS SCHONHERR - PAJN, H. R.; GANDHI, S. S. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1987)
22 species under genus Tanymecus Schonh. have been studied and reallocated under genera Tanymecus Schonh., Esamus Chevr. and Indonecus gen, nov. The study also includes 5 new species which will be reported separately.